2020
DOI: 10.1002/phar.2380
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Interactions between Rifampin and Antihypertensive Drugs Using the Biopharmaceutics Drug Disposition Classification System

Abstract: Study Objective Lack of blood pressure control is often seen in hypertensive patients concomitantly taking antituberculosis medications due to the complex drug‐drug interactions between rifampin and antihypertensive drugs. Therefore, it is of clinical importance to understand the underlying mechanisms of these interactions to help formulate recommendations on the use of antihypertensive drugs in patients taking these medications concomitantly. Our objective was to assess the reliability of the Biopharmaceutics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
0
7
0
4
Order By: Relevance
“…Recommendations based on case study reviews, suggested that, in patients with hypertension when anti-tuberculosis treatment which include rifampicin is started, the use of calcium channel blockers and classes 1 and 2 β-blockers should be avoided. In such patients, use of, Angiotensin-converting enzyme inhibitors (e.g., Ramipril ), Valsartan (Angiotensin II antagonists) and diuretics (like hydrochlorothiazide) should be preferred, as clinically relevant interactions are not expected with these classes of drugs and are shown to be effective [ 51 , 52 ]. Anti-HT drug, Verapamil has been shown to play an important role in the treatment of TB patients in two ways, (i) by transforming non-killing macrophages in to bactericidal, and (ii) improving the therapeutic efficacy of anti-TB drugs by restoring their activity by acting as efflux pump inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations based on case study reviews, suggested that, in patients with hypertension when anti-tuberculosis treatment which include rifampicin is started, the use of calcium channel blockers and classes 1 and 2 β-blockers should be avoided. In such patients, use of, Angiotensin-converting enzyme inhibitors (e.g., Ramipril ), Valsartan (Angiotensin II antagonists) and diuretics (like hydrochlorothiazide) should be preferred, as clinically relevant interactions are not expected with these classes of drugs and are shown to be effective [ 51 , 52 ]. Anti-HT drug, Verapamil has been shown to play an important role in the treatment of TB patients in two ways, (i) by transforming non-killing macrophages in to bactericidal, and (ii) improving the therapeutic efficacy of anti-TB drugs by restoring their activity by acting as efflux pump inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, co-administration with rifampin, an inducer of all the above transporters, may increase valsartan exposure. 124 Concurrent use of atorvastatin and rifampin may result in decreased atorvastatin concentration when administered separately after rifampin or increased atorvastatin exposure when administered simultaneously with rifampin which is due to induction of CYP3A4 metabolism of atorvastatin by rifampin and inhibition of organic anion-transporting polypeptide (OATP1B1)-mediated atorvastatin hepatic reuptake by rifampin, respectively. 125 , 126 Concurrent use of fluvastatin and rifampin may result in decreased fluvastatin effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…los IECA no parecen verse afectados por la rifampicina ya que no son metabolizados por CYP (49) . Cabe mencionar que se ha visto una reducción del AUC del metabolito activo del enalapril (enalaprilato) en un 31%, aunque no están del todo claro y no parecen ser secundarias a esta interacción farmacológica (49) .…”
Section: Inhibidores De La Enzima Convertidora De Angiotensina (Ieca)...unclassified
“…los IECA no parecen verse afectados por la rifampicina ya que no son metabolizados por CYP (49) . Cabe mencionar que se ha visto una reducción del AUC del metabolito activo del enalapril (enalaprilato) en un 31%, aunque no están del todo claro y no parecen ser secundarias a esta interacción farmacológica (49) . De los ARA II, losartán es un sustrato conocido de CYP por lo que se ha observado una reducción del AUC y debería desestimarse como terapia inicial, mientras que para candesartan y valsartan la interacción es poco conocida pero se ha sugerido un aumento de su AUC aunque no es del todo claro (49) .…”
Section: Inhibidores De La Enzima Convertidora De Angiotensina (Ieca)...unclassified